Pagbasa ng panitikan at kulturang popular piling sanaysay, 1976-1996 - Reyes, Soledad S. (Quezon City Ateneo de Manila University Press, 1997)
Criticism on Philippine literature and popular culture in selected writings between 1976 to 1996.
Includes bibliographical references (p. 344-349) and index.
Filipino text
Keywords: Philippine essays; Philippine literature -- 20th century -- History and criticism; Popular culture -- Philippines